Analysis of empowerment level of small embroidery industry - Saifudin Zuhri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
Empowerment and participation are potential ways to enhance economic, social and cultural transformation. The level of empowerment of small and medium industries (IKM) increases their business towards an independent direction which can be seen from aspects of economic power such as access to market information, technology, and facilities for businesses; make decisions in the production distribution and marketing of business results. This research was conducted in the small embroidery industry in Kudus Regency with the aim of the study was to analyze the level of empowerment of the embroidery handicraft small industry in Kudus Regency. The method used is descriptive statistical methods and the level of empowerment which includes economic and non-economic strength is analyzed using the rule of thumb with a sample of 108 small border industry players in Kudus Regency. Business access, market access, technology access, political/lobby access, the role of stakeholders, and business sustainability all show low numbers, so it can be concluded that the level of empowerment of small embroidery industries in Kudus Regency is still low/powerless.